Predictors and short-term outcomes of recurrent pulmonary tuberculosis, Uganda: a cohort study - Kalema, Nelson; Lindan, Christina; Glidden, Dave; Yoo, Samuel D.; atamba, Achilles K; Alfred, Andama; Katagira, Winceslaus; Byanyima, Patrick; Musisi, Emmanuel; Kaswabuli, Sylvia; Ingvar, Sanyu; Zawedde, Josephine; et al. (South African respiratory journal, 2017)
Recurrent tuberculosis (TB) occurring >2 years after completing treatment for a prior TB episode is most often due to reinfection with a new strain of M. tuberculosis. Objectives—We determined the prevalence and outcome of late recurrent TB among hospitalized patients in Kampala, Uganda. Methods—We conducted a retrospective analysis of patients admitted to Mulago Hospital who had cough of >2 weeks’ duration and completed TB treatment >2 years prior to admission. All patients had mycobacterial culture performed on two sputum specimens and vital status ascertained 2-months post-enrollment. We performed logistic regression and Cox proportional hazards modelling to identify predictors of recurrent TB and survival, respectively. Results—Among 234 patients, 84 (36%) had recurrent TB. Independent predictors included younger age (aOR=0.64, 95% CI=0.42-0.97, p=0.04), chest pain >2 weeks (aOR=3.32, 95% CI=1.38-8.02, p=0.007), severe weight loss ≥5 kilograms (aOR=4.88, 95% CI=1.66-14.29, p=0.004) and presence of ≥1 WHO danger sign of severe illness (aOR=3.55, 95% CI=1.36-9.29, p=0.01). Two-month mortality was 17.8% (95% CI=10.5-29.2%), and was higher among patients who were not initiated on TB treatment (aHR=16.67, 95% CI=1.18-200, p=0.04), those who were HIV-positive and not on antiretroviral treatment (aHR=16.99, 95% CI=1.17-246.47, p=0.04) and those with a history of smoking (aHR=1.20, 95% CI=1.03-1.40, p=0.02). Conclusion—The high prevalence of late recurrent TB likely reflects high levels of TB transmission in Kampala. Increased use of empiric TB treatment and early ART treatment initiation if HIV-positive should be considered in patients with a prior history of TB, particularly if they are young, with weight loss ≥5kgs, chest pain >2 weeks or ≥1 WHO danger sign of severe illness.
Keywords: Recurrent TB; Survival; Treatment